Effect of amino acid distribution of amphipathic helical peptide derived from human apolipoprotein A‐I on membrane curvature sensing. Issue 5 (21st January 2013) - Tanaka, Masafumi; Takamura, Yuki; Kawakami, Toru; Aimoto, Saburo; Saito, Hiroyuki; Mukai, Takahiro
Abstract : Amphipathic helix, which senses membrane curvature, is of growing interest. Here we explore the effect of amino acid distribution of amphipathic helical peptide derived from the C‐terminal region (residues 220–241) of human apolipoprotein (apo) A‐I on membrane curvature sensing. This peptide preferred a curved membrane in a manner similar to full‐length apoA‐I, although its model peptide did not sense membrane curvature. Substitution of several residues both on the polar and non‐polar faces of the amphipathic helix had no significant effect on sensing, suggestive of the elaborate molecular architecture in the C‐terminal helical region of apoA‐I to exert lipid efflux function. Abstract : ► The C‐terminal peptide (residues 220–241) of human apoA‐I preferred curved membrane. ► In contrast, its model peptide did not sense membrane curvature. ► Substitution of several amino acid residues had no significant effect on the sensing. ► The C‐terminal region of apoA‐I is finely designed to recognize membrane curvature.